Applying Hope Theory to support middle school transitions. Issue 1 (1st January 2016) - Akos, Patrick; Kurz, Maureen Shields
Abstract: Middle grades transitions pose challenges to many students who meet these tasks with varying levels of success. Contemporary developmental and strengths-based literature offers Hope Theory (Snyder, 2002), a research supported approach that can mitigate risks in school transitions. This article describes how middle grades educators can apply the tenets of Hope Theory to empower students' transition from elementary to middle school, as well as middle to high school.